Influence of Product Quality & Promotion on Purchase Decision with Buying Interest as a Moderating Variable - Ari Soeti Yani; Kristina Ngora (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to determine the effect of product quality and promotion on purchasing decisions with purchase intention as a moderating variable on the customers of UD Santan Kelapa Pasar Serdang Kemayoran. The total population in this study were all consumers of UD Santan Kelapa. The sample in this study was 100 respondents who were obtained through a questionnaire and analyzed using the partial least squares (PLS) data analysis method.sampling technique used was a purposive sampling technique. The results showed that product quality had an insignificant positive effect on purchasing decisions, promotions had no significant positive effect on purchasing decisions, buying interest had a significant effect on purchasing decisions, moderating buying interest on product quality had a positive but not significant effect on purchasing decisions, moderating buying interest on promotion has a positive but not significant effect on purchasing decisions.